1961
DOI: 10.1079/bjn19610012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the plane of energy nutrition of the cow on the secretion in milk of the constituents of the solids-not-fat fraction and on the concentrations of certain blood-plasma constituents

Abstract: An increase in the plane of energy nutrition of the cow is known to increase both the yield and the solids-not-fat (s.N.F.) content of milk: a decrease in fat content also occurs but there is little effect on the yield of fat (for review of literature, see Burt, 1957 a). Though small depressions in milk lactose content occur with underfeeding (Rowland, 1946), any change in S.N.F. content is largely due to a change in the protein content of the milk, and thus an increase in the net energy supply to the cow give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

1961
1961
1995
1995

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 11 publications
4
24
0
Order By: Relevance
“…Changes in concentrations of free amino acids in plasma have been used by Rook & Line (1961) as an index for predicting the adequacy of the diet. They observed that increases in a-amino N levels in plasma were associated with plane of nutrition and milk protein yields.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in concentrations of free amino acids in plasma have been used by Rook & Line (1961) as an index for predicting the adequacy of the diet. They observed that increases in a-amino N levels in plasma were associated with plane of nutrition and milk protein yields.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that content of milk fat was low during glucose infusion is consistent with enhanced lipogenesis in adipose tissue, at the expense of milk fat production, under the influence of elevated levels of plasma insulin (see Annison and McDowell 1980). The higher levels of solids-not-fat in milk of glucose-infused ewes may be explained by increased synthesis of milk protein as a result of the increase in energy supply (Rook and Line 1961).…”
Section: Glucose Biokineticsmentioning
confidence: 99%
“…Dale, Vik-Mo andFjellheim 1979;Espinasse and Ruckebush 1976;Parker 1976) while during reserve storing the NEFA concentrations are lower (Holmes and Lambourne 1970). The practical application of NEFA levels in the blood plasma as the indicator of the energy intake adequacy has, however, been questioned on the basis of homeostatic mechanisms (Rook and Line 1961), the variability of their relationships (Fisher et aI. 1975) and also on the basis of short-term daily fluctuations in NEFA which decrease after feeding and increase with fattening and with mild excitement (Holmes and Lambourne 1970).…”
mentioning
confidence: 99%